The utilization of learning analytics to develop student engagement model in learning management system. (December 2019) - Nizam Ismail, Shahrul; Hamid, Suraya; Chiroma, Haruna
Abstract: Learning Analytics (LA) is evolving learning into a new era of analyzing student's participation and engagement in order to gain some insights. The implementation of LA in a university helps the administration and faculty associates to observe the progress of the students alongside their rate of success. The purpose of this study is to develop a student's engagement model for holistic involvement in the Learning Management System (LMS). The model was developed from an initial model that was derived from the review of literature and existing model of engagement in LMS. The data were collected from the online learning management system of one public University in Malaysia. From the data analysis, it was found that the strong engagement and interaction between the students, lecturers and the content in LMS, led to boost up the usage of the LMS as long as the student participation in the learning environment is accepted, which in return prepared the students to be evaluated anytime. The model that will be developed from this study can help increase the interaction and engagement between lecturers and students in LMS. Unlike the engagement of students in higher education LMS, which has been discussed already in the literature, this research integrated the role of trace data in shaping the learning environment communication and participation of the users.